The dynamics of insurgency - Yap, Romulo F. (1984)
Inherent in all societies in transition are sociological, political and economic dysfunctions that can cause frustrations among certain sectors of the populace. If allowed to build up, these frustrations may be transformed into grievances. Whether these grievances will create an insurgent situation depends on the interaction of accelerators and retardants present in society. Equipped with a vibrant leadership, ideology and cadre system, an insurgent situation may grow into a self-sustaining revolutionary movement with potentially increasing strength.
Keywords: Insurgency; Political participation